Development of novel InDel markers by whole-genome sequence comparison and genetic diversity assessment of Thailand rice blast fungus populations - Napassorn Thamkirati; Worrawit Suktrakul; Athipat Ngernmuen; Theerayut Toojinda; Sureeporn Katengam; Nonglak Parinthawong; Waree Laophermsuk; Pradipha Pradapphai; Watchareeporn Suksiri; Suphattra Janthasri; Chatchawan Jantasuriyarat (My University, 2025)
Abstract InDel markers are commonly used to assess genetic relationships among populations. In this study, we employed a whole-genome sequence comparison method to identify and develop InDel markers for the rice blast fungus Pyricularia oryzae . We analyzed 152 whole-genome sequences of P. oryzae isolates from diverse global regions, including Brazil, Burundi, China, Colombia, Côte d'Ivoire, France, Ghana, Hungary, India, Japan, Korea, Laos, Madagascar, Mali, Morocco, Nepal, the Philippines, Portugal, Spain, Suriname, Thailand, the UK, the USA, and Zambia. Our analysis identified a total of 233,595 InDel loci distributed across the seven chromosomes of P. oryzae . From these, 82 loci were selected based on their high polymorphism across the 152 genome sequences. The effectiveness of these 82 loci was assessed by analyzing the genetic diversity of 47 Thai rice blast isolates alongside two reference isolates, GUY11 (France) and KJ201 (Korea). Of the 82 InDel loci, 33 exhibited polymorphisms, with 2–4 alleles per locus and polymorphic information content (PIC) scores ranging from 0.04 to 0.67. Principal coordinate and structure analyses revealed two genetic subgroups among the Thai rice blast isolates, categorized according to host specificity. Genetic relationships highlighted disparities among rice blast populations based on their respective hosts: rice and grassy weeds. This finding suggests a correlation between genetic relatedness and the plant hosts susceptible to rice blast disease. The newly developed InDel markers provide a valuable resource for future research in this field.
Keywords: Indel; Plant Pathogens and Fungal Diseases